PELUANG PEMILIKAN PERUMAHAN GRIYA PESONA ASRI DI KECAMATAN SIDOHARJO SRAGEN JAWA TENGAH - Unggul Priyadi; Fathya Rahmadhani Zainuri (UII, 2015)
Sidoharjo Sragen is the entrance gate to the Capital District of Sragen. So many Access of the traders passing by in the district of sidoharjo cause of the increasing demand for houses and it also encourages the developers to build housing. This also happens to Griya Pesona Asri which is located at the gate of Sragen. This research is aimed to analyze the influence of housing price, comsumer income, facilities, and the types of jobs towards the opportunities of housing purchase in Griya Pesona Asri.The analytical tool which is used is LPM (Linear Probability Model) regression. The respondents in this study are the residents of Griya Pesona Asri. The results show that the price of the housing gives significant and negative effects towards the modest housing purchase opportunities or the other than modest in Griya Pesona Asri. The income of the customers has negative effect and significant on the modest housing purchase opportunities or the other than modest in Griya Pesona Asri.Keywords: LPM, Housing Purchase Opportunities, Griya Pesona Asri